A study of pathological lesions in European badgers (Meles meles) with and without mycobacteriosis in England (northern Edge area) - Corbetta, Davide (2020)
European badgers (Meles meles) are omnivores members of the family Mustelidae and are widely present in all Europe and the United Kingdom. They are believed to play an important role in the epidemiology of bovine tuberculosis (bTB) in England and several other European countries. Previous studies focused on badgers from cattle bTB endemic areas. European badgers (Meles meles) are also known to be infected by a wide range of other bacterial, viral, protozoal and parasitic diseases. The aim of this study was to evaluate non-traffic-injury-related macroscopic and histological lesions in road-killed badgers with and without mycobacteriosis from the northern edge of the bTB epidemic, which is considered an area of lower bTB prevalence.